2000
DOI: 10.1002/1097-0215(20001001)88:1<12::aid-ijc3>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 expression is up-regulated in pancreatic but not in other gastrointestinal cancers

Abstract: Syndecan‐1 belongs to the syndecan family of cell surface transmembrane heparan‐sulfate proteoglycans, which participate in cell proliferation, cell migration and cell‐matrix interactions. Decreased expression of syndecan‐1 has been observed in some gastrointestinal malignancies, and it is thought that high levels of syndecan‐1 correlate with the maintenance of epithelial morphology and inhibition of invasiveness. In our study, we characterized the expression of syndecan‐1 in normal, chronic pancreatitis and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
83
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(85 citation statements)
references
References 43 publications
(79 reference statements)
1
83
0
Order By: Relevance
“…Consistent with this, overexpression of syndecan-1 has bee shown to induce approximately a twofold increase in the proliferation of endometrial cancer cells (26). Syndecan-1 mRNA levels are up-regulated in pancreatic cancer in association with accelerated tumor growth, as determined by in situ hybridization and immunohistochemistry (27).…”
Section: Syndecans and Cancermentioning
confidence: 54%
“…Consistent with this, overexpression of syndecan-1 has bee shown to induce approximately a twofold increase in the proliferation of endometrial cancer cells (26). Syndecan-1 mRNA levels are up-regulated in pancreatic cancer in association with accelerated tumor growth, as determined by in situ hybridization and immunohistochemistry (27).…”
Section: Syndecans and Cancermentioning
confidence: 54%
“…41 Overexpression of integrins and the HSPGs syndecan-1 and glypican-1 on pancreatic cancer will mediate transduction by Ad5 and will thus lower the effect of retargeting strategies. 7,42,43 However, because these proteins will also have an important function in vivo the targeting seen in these slices will reflect the efficacy of retargeting of this vector in patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that syndecan-1 promotes the metastases in lung squamous carcinoma cells (Hirabayashi et al, 1998). The overexpression of syndecan-1 expression has been observed in various cancer such as pancreatic (Conejo et al, 2000), gastric (Wiksten et al, 2001) and breast (Stanley et al, 1999;Barbareschi et al, 2003;Burbach et al, 2003) carcinomas.…”
Section: Soluble Syndecans and Tumormentioning
confidence: 99%